Validity of the Corporate Edition Flip PDF Assisted Learning E-Module for Improving Students' Critical Thinking Skills - Imara, Salsabila Yulia; Rusmini (Universitas Pendidikan Mandalika, 2025)
The rapid development of 21st-century technology demands that students possess critical thinking skills as one of their core competencies. To support the achievement of this competency, innovative, interactive, and relevant learning media are needed. This research is a Research and Development (R&D) study that aims to develop and test the content and construct validity of a Problem-Based Learning (PBL)-based e-module on Thermochemistry material, assisted by Flip PDF Corporate Edition. The development model used is 4D (Define, Design, Develop, Disseminate), but this research is limited to the develop stage. The main focus of the research lies in the validity aspects of the e-module, both in terms of content and construct, covering aspects of content suitability, language, presentation, and graphics. The instrument used was a validation sheet, assessed by three expert validators in chemistry education and instructional material development. The validation results indicate that the e-module is in the valid category, with a modal score of 4, which falls into the good category. This validation process was conducted to ensure that the developed e-module meets the feasibility standards as an interactive learning medium capable of fostering students' critical thinking skills. The findings from this validation stage will then serve as the basis for refining the e-module before it is piloted on a limited number of students.